Palladium-Catalyzed Regioselective Synthesis of Oxygenated Biphenyls - Chittimalla, Santhosh Kumar; Kuppusamy, Rajesh; Akavaram, Naresh (Synlett, 2015)
Palladium-catalyst-mediated Michael addition reaction of arylboronic acids to cyclohexa-2,4-dienones followed by aromatization sequence in one-pot furnished several oxygenated biphenyl derivatives. Application of the developed methodology was successfully applied to the synthesis of biphenyl natural products aucuparin and 2′-hydroxy-3,4,5-trimethoxybiphenyl.
Keywords: biphenyls; cyclohexa-2,4-dienones; arylboronic acid; tandem reactions; natural products